Development of sustainable material for hybrid wall system to improve indoor thermal performance - Narendra raut, Ashwin (2017)
Thermal performance of building envelope has been of great importance in determining the indoor thermal environment mainly due to the impact of existing global warming issues. Due to the hot and humid climate of Malaysia, and poor thermal design of building envelope, mechanical cooling of buildings is becoming almost a necessity. This necessity in the case of low-income home owners is an added burden. Thus there is a need to provide wall system with better thermal performance than conventional wall systems. Due to the emphasis on developing sustainable built environments, researchers are striving for waste incorporation in building wall material. However, the waste incorporated within the building wall system, especially in bricks still lacks practical applicability when it comes to the overall performance of the system in terms of mechanical, thermal and physical properties. The focus of the research is to tackle the twin issues of sustainability and thermal performance of building wall systems for affordable homes using a Design Science methodology. A cost-effective sustainable alternative building wall system with better thermal performance than conventional material is proposed by utilizing locally available waste materials such as waste glass and oil palm industry byproducts. The enhancement of thermal performance of wall materials was done by the introduction of cellular porous palm oil fibers to lower the heat transfer. Fiber reinforced mortar (FRM) and thermally enhanced sustainable hybrid (TESH) bricks were developed by optimizing the mix design using Glass Powder, Palm Oil Fly Ash and Oil Palm Fibers based on Taguchi’s Process Parameter approach. Both the FRM and TESH bricks, which constitute the thermally enhanced sustainable hybrid (TESH) wall system, were analyzed for physical, mechanical and thermal performance and they comply with the various codes of practice for building materials. ANSYS WORKBENCH software was used to determine the thermal performance of the newly developed TESH. The temperature distribution and rate of heat transfer through the wall system was found to be significantly lower than conventional wall systems. Also, comparative energy analysis established that the energy consumption is 10.6 % lower for TESH. Due to the lower electricity consumption, the total energy costing for the building was also reduced by 10.2 %. Thus, TESH proves to be more sustainable and cost effective within the operational phase of the building. TESH is a sustainable alternative for low-cost housing units due to its proven low embodied energy as it comprises mainly of locally available waste materials for its production.